Effects of explicit lexical collocation instruction on non-English major students' writing performance - Cao Yến Ngọc (Trường Đại học Trà Vinh, 2022)
To fill in the gap mentioned above, this study has been conducted to shed light on the effects of explicit lexical collocation instruction on non - English major students’ vocabulary used and their writing performance. Moreover, this paper explores the students’ attitudes on the explicit instruction of lexical collocation regarding their writing performance.